Forewarned is Forearmed how Climate Information Services are Saving the Lives and Livelihoods of Senegalese Fisherfolk - Issa Ouédraogo (Food and Agriculture Organization of the United Nations, 2018)
A success story from the USAID / CINSERE project exhibited in the Innovation Fair organized by the Food and Agriculture Organization (FAO) at Rome, Italy from 21 and 22 November 2018.